Multimedia Presentation Systems (MPS) - Mohd Noor, Mohd Fakhri (Universiti Teknologi Petronas, 2004)
The purpose of this research and software development is wanted to enhance the content deliverance of the knowledge among the UTP community. Directly to that reasons, the Multimedia presentations system hopefully will fulfilled this purpose. This research paper will be started on discussing about the problem statement of this project. Problem statement will be referred by the author as a material for the use of analyzing and designing the requirement of the systems. This paper will also discuss about the methodology which been used throughout the entire of development process of the system This project paper will discuss more on the hybrid methodology as the overall process of system development is based on this methodology. As the process of developing the system is nearing to the completion stage, the overall performance of this system will be discuss on the discussion and result part of this paper. That part will discuss about the problem which occurred during the development of the process and series of testing for the system As a conclusion, this project will be referred as new tools of combined technology of information deliverance for the UTP community. This project will be a starting point of enhancing the ways of interaction between the lecturer and student during their study.